Chemically modified cellulose as a potential oil adsorbent of contaminated marine ecosystems - Madeira, Aline Amaral; Silva, Ana Luiza Coimbra; Dias, Brenda Martins; Pena, Camila Andrade; Oliveira, Raphael Victor Costa (Eclética Química, 2020)
Petroleum exploration, as well as environmental impacts descendant of aquatic contaminations involving sea oil spills, foments the development of new technologies of marine ecosystems protection. Acknowledged like the most abundant polymer available today worldwide, cellulose is a linear 1.4-β-glucan, composed of D-anhydroglucopyranose units, linked together by β-(l→4)-glycosidic bonds. In this study, a chemical modification route of the cellulose polymer was accomplished using glycidyl methacrylate and stearin to test its oily adsorption capacity of soybean, diesel, and residual oils. Scanning Electron Microscopy (SEM) and Fourier-Transform Infrared (FT-IR) Analyses were applied to the characterization of the morphological and functional structure of microcrystalline cellulose. The results obtained proved the reach of an average hydrophobicity grade of 78.3±0.9% and a mass gain of MG = 2.89%, suggesting the possible insertion of hydrophobic groups onto the cellulose molecule and corroborating the hypothesis of successful grafting of glycidyl methacrylate and stearin onto the polymer. The oily adsorption tests showed a satisfactory capacity of the modified cellulose to adsorb small amounts of viscous oils, like residual oil.